Preparation of Activated Carbons with High Surface Area from Wood Charcoal Powder by Dry Chemical Activation - อยู่มี, พิทักษ์ (KKU Science Journal, 2015)
Wood charcoal powder was used to prepare high surface area activated carbon by dry chemical activation method. Optimum activation conditions i.e. activation reagent and wood charcoal powder ratios, activation temperatures and activation times were investigated. The experimental results showed that the weight ratio between wood charcoal powder and NaOH as 1:3, activation temperature of 600 °C and activation time of 2 hours gave the highest surface area product. The activated carbon production under optimum conditions had an iodine number of 1,247 mg/g and BET surface area of 1,214.52 m2/g. The activated carbon was also characterized by FT-IR, XRD and SEM. Therefore, the preparation of activated carbon by dry chemical activation has several benefits i.g. it is cheap, simple and it provide high surface area products